Analisis risiko dengan value at risk (VAR) - exponential generalized autoregressive conditional heterokedasticity in mean (EGARCH-M) - Tria Rosdiana (Fak. Sains dan Teknologi UIN Sunan Kalijaga, 2016)
oen, 1/irh,c.1